2022
DOI: 10.1177/21582440221095010
|View full text |Cite
|
Sign up to set email alerts
|

A Study on How Psychological Capital, Social Capital, Workplace Wellbeing, and Employee Engagement Relate to Task Performance

Abstract: The current study was conducted to examine the relationship between Psychological capital (PsyCap), Social capital, Workplace wellbeing, and Employee engagement in Saudi Arabia. Only limited evidence exists about the relationship between the constructs in Saudi Arabia. Data was collected from 395 gainfully employed Saudi samples, using five standardized and validated questionnaires. The data was analyzed using Exploratory and Confirmatory Factor Analysis and Structural Equation Modeling (SEM). SEM was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 157 publications
(249 reference statements)
0
5
0
1
Order By: Relevance
“…Allam (2017) highlighted that the employee disengagement is real threat to an organization. Similarly, Al-Kahtani and MM (2022) identified that the HRM practices are playing imperative role in the development of positive attitude of employees. Thus, humble leaders, by acknowledging mistakes and limitations, recognizing the contributions and strengths of followers, and modeling teach ability can create an environment in which followers can feel obliged and fully engage in their work.…”
Section: Discussionmentioning
confidence: 99%
“…Allam (2017) highlighted that the employee disengagement is real threat to an organization. Similarly, Al-Kahtani and MM (2022) identified that the HRM practices are playing imperative role in the development of positive attitude of employees. Thus, humble leaders, by acknowledging mistakes and limitations, recognizing the contributions and strengths of followers, and modeling teach ability can create an environment in which followers can feel obliged and fully engage in their work.…”
Section: Discussionmentioning
confidence: 99%
“…Through motivating stimuli, workers’ PsyCap levels and changes can be transformed into beneficial organizational behaviors (Alessandri et al, 2018). Transformational leadership is seen as an external resource that spurs followers’ internal psychological resources (Al Kahtani & Sulphey, 2022; Halbesleben & Wheeler, 2015; Ten Brummelhuis et al, 2011). This idea is rooted in the cross-sectional field study by Gooty et al (2009), showing that PsyCap mediates between transformational leadership and follower in-role performance.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…By means of this norm, transformational leaders trigger their followers’ resource base (Shamir et al, 1993) which in turn is known to be conducive to high follower job performance. Next to this follower-felt support for excellence, PsyCap is examined here as another psychological resource through which transformational leadership may affect not only follower job performance but also work engagement (Al Kahtani & Sulphey, 2022; Gooty et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological capital plays an important role in the process of business development, influence business performance directly or indirectly through various factors (Ngo, 2021;Jiao et al, 2022), task performance (Udin and Yuniawan, 2020;Al Kahtani and Sulphey, 2022), project performance , safety performance , entrepreneurial performance (Gao et al, 2020a), and business performance (Chen and Tao, 2021) of the firm. With the increasing importance of innovationdriven strategy in enterprise development, the path to improve enterprise innovation performance has become a hot spot for scholars' research, and psychological capital as a variable affecting innovation performance has been included in scholars' analytical models (Guo et al, 2020), mediated by the intrinsic motivation of the transformational educational environment, and shown through empirical studies that workers' psychological capital is positively related to innovation performance (Tran et al, 2021).…”
Section: Data Availability Statementmentioning
confidence: 99%